To cut or not to cut, that is the question: A review of the anatomy, the technique, risks, and benefits of an episiotomy. Issue 3 (April 2017) - Muhleman, Mitchel Alan; Aly, Islam; Walters, Andrew; Topale, Nitsa; Tubbs, R. Shane; Loukas, Marios
Abstract : Childbirth can be a traumatic experience on the female body. Some techniques may be implemented to make the process smoother and decrease the potential lacerations that can occur. Episiotomies have been used by obstetricians and midwives to help make the fetal decent down the vaginal canal less turbulent. A physician must use his best judgment on when it is necessary to make this incision and what form of incision to make. Before making an incision one must understand the female external and internal anatomy and thoroughly comprehend the stages of birth to understand how and what complications can occur. Even though an episiotomy is a minor incision, it is still a surgical incision nonetheless and as with any form of surgery there are both risks and benefits that are to be considered. Nevertheless, episiotomies have proven to help ease births that are complicated by shoulder dystocia, prevent severe lacerations, and decrease the second stage of labor. The following comprehensive review provides a description of the female anatomy, as well as an extensive description of why, when, and how an episiotomy is done. Clin. Anat. 30:362–372, 2017. © 2017 Wiley Periodicals, Inc.